The humanistic and societal impact of obesity in Japan: a targeted literature review - Wataru Ogawa; Palvi Gupta (Endocrine Journal)
Obesity is a focus of Japanese public health policy, due to Japanese individuals’ high susceptibility to weight-related conditions. In contrast to global definitions, obesity is defined as a body-mass-index (BMI) of ≥25 kg/m2 in Japan. Despite public efforts, rates of obesity have not decreased over the past decade. To better understand its societal impact, we examined the economic, quality of life (QoL), and complications burden of obesity in Japan. Electronic databases were searched for English and Japanese-language publications from 2005 to December 2020 reporting on adults with obesity in Japan; other diseases were excluded, with no restriction on intervention. Outcomes of interest included costs or resource use, QoL, risk of complications, and other clinical outcomes. We identified 137 studies, including 19 reporting on economic evidence, eight reporting on QoL, and 115 reporting on the relationship between obesity and the risk of complications or mortality. The studies consistently showed that Japanese adults with obesity (BMI ≥25 kg/m2) are at increased risk of complications vs. normal weight adults. They also confirmed higher total and medical costs, resource use, and hospitalization costs among adults with obesity vs. normal weight adults. In addition, the studies confirmed a considerable impact of obesity on physical and mental aspects of QoL. Overall, this study found that obesity in Japan is associated with a substantial burden. Japanese people are at risk even with BMI ≥25–<30 kg/m2, which are generally considered as pre-obese in other countries.